Distribution of HIV test devices in developing countries - Curtis N. Vanderpuije (2014)
The distribution of HIV test devices in the developing world context is an interesting problem that poses numerous challenges. This project delves into the dire situation in Zambia, explores the underlying issues of the HIV pandemic and develops potential distribution models for the HIV test devices. The model looks at potential distribution channels for the Oraquick® product - a relatively new point-of-care test device for HIV. The model is used to explore a fully centralized and a fully decentralized distribution model A hybrid model is then proposed for the distribution of the devices within the country. The model is generic and gives an approximate answer instead of an exact solution. The generic nature of the model makes it easy to modify for potential studies in other countries and can be further expounded for distribution of other health care related products as well.